2012
DOI: 10.1377/hlthaff.2012.0359
|View full text |Cite
|
Sign up to set email alerts
|

Colorado’s Patient-Centered Medical Home Pilot Met Numerous Obstacles, Yet Saw Results Such As Reduced Hospital Admissions

Abstract: The Colorado Multipayer Patient-Centered Medical Home Pilot, which ran from May 2009 through April 2012, was one of the first voluntary multipayer medical home pilot projects in the country. Six health plans, the state's high-risk pool carrier, and sixteen family or internal medicine practices with approximately 100,000 patients participated. Although a full analysis is currently under way, preliminary results show that the pilot significantly reduced emergency department visits and also reduced hospital admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 1 publication
0
49
0
Order By: Relevance
“…Several multipayer PCMH pilots provide a "management fee" (based on panel size) to participating providers. 22,23 For example, Horizon Healthcare in New Jersey pays "coordination fees" that vary with the type of patient. 24 …”
Section: Value-based Supplemental Paymentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several multipayer PCMH pilots provide a "management fee" (based on panel size) to participating providers. 22,23 For example, Horizon Healthcare in New Jersey pays "coordination fees" that vary with the type of patient. 24 …”
Section: Value-based Supplemental Paymentsmentioning
confidence: 99%
“…Successful payment reform requires providers and payers to collaborate and coordinate and may be impeded by the many contentious and competitive relationships among stakeholders. 10,23,28,29 For example, bundled or global payments require that stakeholders agree on the type of payment and means of sharing risk and payment, as well as the metrics for measuring performance. Concerns about potential financial losses and inequitable sharing of risk may keep them from reaching a consensus.…”
Section: Implementation Processmentioning
confidence: 99%
“…Fortunately, early results are promising, with some sites showing reduced patient emergency department visits and hospitalizations, 6 and improved patient empowerment and satisfaction. 7 One insurer recently reported a significant positive return on investment.…”
Section: Ethics and Implementationmentioning
confidence: 99%
“…For example, a variety of evaluation designs carried out in different medical home practices have produced reductions in ED visits and hospital admissions for a general adult primary care population and for populations of patients who have chronic conditions, are older than sixty-five, or both. [14][15][16][17][18] An exception is a study of the Pennsylvania Chronic Care Initiative that compared use and quality results over three years for thirty-two patient-centered medical homes and twentynine control practices that volunteered to participate in the study, and that found no significant changes in the use of the ED or inpatient services. 19 An accompanying editorial by Thomas Schwenk pointed out that volunteerism introduced a number of potential confounders.…”
Section: Discussionmentioning
confidence: 99%